Correlation of PD-L1 immunohistochemical expression with microsatellite instability and p53 status in endometrial carcinoma. (December 2022) - Arafa, Mohammad; Shebl, Abdelhadi Mohamed; Salama, Amany; ElZahaf, Eman; Ashamallah, Sylvia A.; Foda, Abd AlRahman; Awad, AzmyAbd El-Hameed; Shalaby, Asem
Abstract: Background: Endometrial carcinoma (EC) is the most common gynaecological cancer worldwide. The Cancer Genome Atlas molecular grouping of a given case of EC could be assessed by POLE gene mutation, mismatch repair (MMR) 'to reflect microsatellite instability' and p53 status, which has proved to be of prognostic value. Programmed cell death receptor 1 (PD-1) and its ligand (PD-L1) are playing a progressively important role in tumour immunology and cancer treatment. Objectives: To investigate PD-L1 immunohistochemical expression in EC in relation to MMR and p53 status. Associations between marker expression and different histopathological parameters were also investigated. Methods: This retrospective study was performed on archival biopsies of 170 cases of EC using a tissue microarray model. Immunohistochemical staining was applied using antibodies against PD-L1, MLH1, MSH2 and p53. Results: The percentages of positivity were as follows: PD-L1, 19.6%; MLH1, 79.5%; MSH2, 78.5%; and p53 mutant, 13.8%. There was significant correlation between MLH1 expression and MSH2 expression ( p = 0.008). Tumour grade was significantly correlated with stage ( p = 0.005) and p53 mutant expression ( p = 0.008). Combined PD-L1 positivity and MMR deficiency showed significant correlation with the presence of lymphovascular space invasion (p = 0.014). MSH2 negativity was significantly associated with poorer overall survival ( p = 0.014). Conclusions: A panel of immunohistochemical markers (PD-L1, MLH1, MSH2 and p53) could help to predict the prognosis and plan the treatment of patients with EC. MMR deficiency seems to be a good predictor for PD-L1 status, and therefore the response to potential PD-1/PD-L1 inhibitor therapy.